PENGARUH KESELAMATAN KERJA DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. AEROFOOD CATERING SERVICE DIVISI LAUNDRY TANGERANG - Rahmi Hermawati; Mariza Mariza (universitas Pamulang, 2019)
This study shall aim inestablishing the effect of work safety as well as the training on performance at PT Aerofood Catering ServiceLaundry Division, to specify the effect of training on the performance of employees of PT Aerofood Catering Service Laundry division, and to find out how much influence work safety and training shall impact on performance of employees of PT Aerofood Catering Service Laundry division collectively.The population and sample of this study shall be 50 respondents who are employees of PT Aerofood Catering Service Laundry division. The variables in this study consist of Occupational Safety (X1) and Training (X2) as independent variables while Employee Performance (Y) as the dependent variable. The method of data collecting shall be using observation, questionnaires and interviews. Data analysis shall be using multiple linear regression, analysis of product moment coefficient test, Test coefficient of determination (kd), significance test both partially (t test) and simultaneously / together (test f).In accordance with the results of the study, the variable Safety at PT Aerofood Catering Service Laundry division which shall be categorized as Good while Training variable at PT Aerofood Catering Service Laundry division shall be categorized as Good and Employee Performance variable at PT Aerofood Catering Service Laundry division shall be categorized as GOOD. There is a positive influence between Work Safety and Training on Employee Performance with a regression value of 5,029X1 and 2,107X2. The value of the correlation coefficient (r) shall be 0.997. This means that work safety and training variables have a very strong relationship to employee performance and the value of determination (Kd) of 0.998, It can be concluded that work safety (X1) and training (X2) on employee performance (Y) shall be 99.8% while the rest of 0 , 4% shall be influenced by other factors. Obtained Work Safety (X1) t value or t table (5.629> 1.677), this is also reinforced by a significance value of 0.000 <0.05, it can be said to be significant. This means that Ho shall be rejected and H1shall be accepted, which means, there is a positive and significant influence between training on employee performance. While the value of t count Training (X2)> t table or (25,666> 1,677), this is also reinforced with a significance value of 0,000 <0,05, so it can be said to be significant. This means that Ho is rejected and H1 is accepted, which means there is a positive and significant influence between training on employee performance. The value of F count> F table or (5886.67> 2,800), this shall be also reinforced by a significance value of 0,000 <0,05, so that it can be said to be significant. This means that Ho shall be rejected and Ha shall be training on performance. Keywords: Work Safety, Training and Performance